Determining the drift potential of Venturi nozzles compared with standard nozzles across three insecticide spray solutions in a wind tunnel - Ferguson, J. Connor; Chechetto, Rodolfo G. [UNESP]; O'Donnell, Chris C.; Dorr, Gary J.; Moore, John H.; Baker, Greg J.; Powis, Kevin J.; Hewitt, Andrew J. (Wiley-Blackwell, 2016)
BACKGROUNDPrevious research has sought to adopt the use of drift-reducing technologies (DRTs) for use in field trials to control diamondback moth (DBM) Plutella xylostella (L.) (Lepidoptera: Plutellidae) in canola (Brassica napus L.). Previous studies observed no difference in canopy penetration from fine to coarse sprays, but the coverage was higher for fine sprays. DBM has a strong propensity to avoid sprayed plant material, putting further pressure on selecting technologies that maximise coverage, but often this is at the expense of a greater drift potential. This study aims to examine the addition of a DRT oil that is labelled for control of DBM as well and its effect on the drift potential of the spray solution. The objectives of the study are to quantify the droplet size spectrum and spray drift potential of each nozzle type to select technologies that reduce spray drift, to examine the effect of the insecticide tank mix at both (50 and 100 L ha(-1)) application rates on droplet size and spray drift potential across tested nozzle type and to compare the droplet size results of each nozzle by tank mix against the drift potential of each nozzle. RESULTSThe nozzle type affected the drift potential the most, but the spray solution also affected drift potential. The fine spray quality (TCP) resulted in the greatest drift potential (7.2%), whereas the coarse spray quality (AIXR) resulted in the lowest (1.3%), across all spray solutions. The spray solutions mixed at the 100 L ha(-1) application volume rate resulted in a higher drift potential than the same products mixed at the 50 L ha(-1) mix rate. The addition of the paraffinic DRT oil was significant in reducing the drift potential of Bacillus thuringiensis var. kurstkai (Bt)-only treatments across all tested nozzle types. The reduction in drift potential from the fine spray quality to the coarse spray quality was up to 85%. CONCLUSIONThe addition of a DRT oil is an effective way to reduce the spray solution drift potential across all nozzle types and tank mixes evaluated in this study. The greatest reduction in drift potential can be achieved by changing nozzle type, which can reduce the losses of the spray to the surrounding environment. Venturi nozzles greatly reduce the drift potential compared with standard nozzles by as much as 85% across all three insecticide spray solutions. Results suggest that a significant reduction in drift potential can be achieved by changing the nozzle type, and can be achieved without a loss in control of DBM. (c) 2016 Society of Chemical Industry
Keywords: spray drift; wind tunnel; insecticides; diamondback moth; nozzles; drift reduction technologies